2019
DOI: 10.1093/molehr/gaz016
|View full text |Cite
|
Sign up to set email alerts
|

ATM expression is attenuated by promoter hypermethylation in human ovarian endometriotic stromal cells

Abstract: A number of genes involved in the pathogenesis of endometriosis are silenced by the hypermethylation of their promoter regions. We assessed the effect and mechanism of the DNA demethylating agent 5-aza-2-deoxycytidine (5-aza-dC) (10 μM) on the cell cycle in human endometriotic cyst stromal cells (ECSCs) and normal endometrial stromal cells (NESCs) by flow cytometry. The DNA methylation status of G2/M checkpoint regulators were investigated by methylation-specific PCR. The expression of ataxia telangiectasia mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Indeed, immunohistochemistry of ATM protein expression in lung adenocarcinoma revealed that over 40% had low protein expression, despite only 10% showing gene mutation 48 . In addition, ATM promoter methylation has been shown to lead to silencing in some cancer cells 49,50 . Therefore, it is possible that more patient samples may lack ATM expression or function than indicated by exome sequencing and that methods for assaying ATM protein expression and/or activity will be required for patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, immunohistochemistry of ATM protein expression in lung adenocarcinoma revealed that over 40% had low protein expression, despite only 10% showing gene mutation 48 . In addition, ATM promoter methylation has been shown to lead to silencing in some cancer cells 49,50 . Therefore, it is possible that more patient samples may lack ATM expression or function than indicated by exome sequencing and that methods for assaying ATM protein expression and/or activity will be required for patient selection.…”
Section: Discussionmentioning
confidence: 99%
“…SLC5A8 has been shown to be a tumor suppressor in lung tumor and silenced by promoter hypermethylation in the development of lung cancer (52). Several studies have reported that there are some genes with aberrant DNA methylation in promoter regions in endometriosis, such as HOXA10 (53) and ATM (54). Taken together, these reports reveal that DNA methylation is implicated in the development of disease.…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, immunohistochemistry of ATM protein expression in lung adenocarcinoma patient samples revealed that over 40% had low protein expression, despite only 10% showing gene mutation (Villaruz et al 2016). In addition, promoter methylation has been shown to lead to ATM gene silencing in some cancer cells (Hirakawa et al 2019;Kim et al 2002;Jette et al 2020). Therefore, it is possible that more patient samples may lack ATM expression or function than indicated by exome sequencing alone and that methods for assaying ATM protein expression and/or activity will be required for patient selection.…”
Section: Discussionmentioning
confidence: 99%